Pengaruh Orientasi Pasar dan Inovasi Produk Terhadap Kinerja Bisnis UMKM di Provinsi Lampung dengan Halal Supply Chain Sebagai Variabel Moderasi - Siti Maisaroh; Syamsul Hilal; Hanif Hanif (Jurnal Ilmiah Ekonomi Islam, 2022)
Currently, attention to the performance of MSMEs is very high because it can help remove blockades and generate broad prospects for MSMEs to develop as well as to compete strongly in regional and global markets. Therefore, business actors are very responsible for managing MSMEs and trying to get MSMEs that are better than the performance generated by implementing Market Orientation and Product Innovation. Halal Supply Chain is information that flows in every supply chain must be in accordance with the principles of sharia law. It is known that Indonesia is a country with a majority Muslim population. Therefore, awareness of the importance of applying Islamic law in living life, makes Muslim communities in Indonesia instill the concept of halal in their daily lives. Based on this, the researchers conducted this study to find 4 things, namely Does Market Orientation and Product Innovation have a partial significant effect on MSME Business Performance in Lampung Province? Do Market Orientation and Product Innovation partially affect business performance with Halal Supply Chain as a moderating variable MSMEs in Lampung Province?, Does Market Orientation and Product Innovation have a Partially Significant Effect on MSME Business Performance in Lampung Province?, Do Market Orientation and Product Innovation have a significant effect on business performance with Halal Supply Chain as a moderating variable on MSMEs in Lampung Province? The method used in this study is a quantitative research method. The data used in this study is primary data derived from the results of the questionnaire answers that will be distributed to the MSME actors in Lampung Province. The sample used uses the Probablily Sampling Technique with the sample results used by 100 MSME actors in Lampung Province.The results of this study found that the percentage of Halal Supply Chain reinforcement as a moderating variable has a different effect seen based on the T test (Partial) that Market Orientation and Product Innovation have no significant effect on MSME Business Performance with Halal Supply Chain as a moderating variable while based on the results of the F test (Simultaneous) that Market Orientation and Product Innovation have a significant effect on MSME Business Performance.